Pro IOS and Android Apps for business - Zammetti, Frank W.
With Pro iOS and Android Apps for Business, you can take your web development experience and apply it toward creating a full-featured business app, from soup to nuts. Frank Zammetti shows you how to create a client app using jQuery Mobile wrapped in PhoneGap, and how to create a node.js-based server that uses MongoDB as its data store